2015
DOI: 10.1007/s13277-015-3061-7
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 is an independent predictor of outcome in basal-like triple-negative breast cancers treated with adjuvant anthracycline-based chemotherapy

Abstract: Neither targeted therapies nor predictors for chemotherapy sensitivity are available for triple-negative breast cancer (TNBC). Our study included 187 patients with TNBC, 164 of whom were treated with anthracycline-based adjuvant chemotherapy. Eleven molecular biomarkers were analyzed. BCL2, epidermal growth factor receptor (EGFR), MYC, TOP2A, and Ki-67 protein expression was evaluated by immunohistochemistry. The status of the EGFR, MYC, and TOP2A genes and chromosomes 7, 8, and 17 was assessed using fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
2
24
1
2
Order By: Relevance
“…Although the expression levels of Ki-67, BCL2 and p53 in TNBC have been reported as a prognostic marker for TNBC in previous studies (Adamo and Anders, 2011;Abdel-Fatah et al, 2013;Bouchalova et al, 2015;Keam et al, 2011), we did not observe significant associations between the expression of these proteins and the PFS of TNBC patients in our study, probably due to limited events in our study.…”
Section: Association Between S100p and Hyal2 Expression And Progressicontrasting
confidence: 96%
“…Although the expression levels of Ki-67, BCL2 and p53 in TNBC have been reported as a prognostic marker for TNBC in previous studies (Adamo and Anders, 2011;Abdel-Fatah et al, 2013;Bouchalova et al, 2015;Keam et al, 2011), we did not observe significant associations between the expression of these proteins and the PFS of TNBC patients in our study, probably due to limited events in our study.…”
Section: Association Between S100p and Hyal2 Expression And Progressicontrasting
confidence: 96%
“…Choi et al [29] reported that although BCL2 expression was not associated with any clinicopathologic parameters and did not affect patient survival in TNBC, BCL2 expression showed a significant association with worse OS and disease free survival in the nonbasal (claudin-low; CK5/6– and EGFR–) subgroup of TNBC [29]. Bouchalova et al [30] reported that high BCL2 expression is a significant independent predictor of poor outcomes in TNBC patients treated with anthracycline-based adjuvant chemotherapy, and high EGFR protein expression is associated with poor BCSS in patients with TNBC treated with anthracycline-based chemotherapy, especially in basal-like (core; CK5/6+ and/or EGFR+) TNBC [30]. Further investigations will be required to elucidate the prognostic association between BCL2 and TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between Bcl-2 expression and patient outcome has been the focus of a number of studies on primary breast cancer and, paradoxically, Bcl-2 was identified to be a marker of improved prognosis (45) across molecular subtypes (4649). The explanation for this paradox may be that Bcl-2 is an estrogen-responsive gene (50) or that high levels of pro-apoptotic Bcl-2 trigger mitochondrial priming (51).…”
Section: Discussionmentioning
confidence: 99%